Energy Production from Sewage Sludge in a Proposed Wastewater Treatment Plant - Mohamed Ayoub; Ibrahim Gar Al-Alm Rashed; Ahmed El-Morsy (Civil Engineering Journal, 2016)
The implemented technologies for sewage sludge processing are still very limited in Egypt. Unfortunately, dealing with the produced sludge is mainly given to the drying process through natural drying beds neglecting quality of the dried sludge. The undertaken work is devoted to provide a design proposal for a typical wastewater treatment plant suitable for the small communities on a very limited area of land compared to that required to construct the conventional treatment plant that serves the same population. The proposed sewage treatment plant is certainly beneficial in reducing the capital costs by 26%, in addition to about 20% reduction in the running costs. On the other hand, electricity generated from energy produced by anaerobic digestion of sewage sludge reduces the electrical power requirements from the main grid network to about 27% in the proposed wastewater treatment plant.